“Garrando nojo do powerpoint”: discursos sobre práticas de letramentos acadêmicos em uma comunidade de prática em ensino de artes visuais - Scherer, Anelise Scotti (2017)
This study (register GAP/UFSM n. 034521) is part of the umbrella project PQ-CNPq Letramento acadêmico/científico e participação periférica legítima em comunidades de produção de conhecimento (register CAAE/UFSM 21033613.2.0000.5346), coordinated by professor Désirée Motta-Roth. Its objective is to map academic literacy practices of a community of knowledge production in Visual Art Education (CPVAE) in a Brazilian federal university. Three issues are central to this mapping: system of academic activities, discursive genres that constitute these activities and the participants’ legitimate peripheral participation (LPP) (LAVE; WENGER, 1991) in this system through the analysis of their discourses on the genres and activities. As part of the umbrella project, we adopt the theoretical and methodological framework of two associated approaches: critical literacies (CERVETTI; PARDALES; DAMICO, 2001) and Critical Genre Analysis (MEURER, 2002; BHATIA, 2004; MOTTA-ROTH, 2006; 2008), which inter-relate principles and concepts of Systemic-Functional Linguistics (p. ex. HALLIDAY, 1978; HALLIDAY; HASAN, 1989), Socio-Rhetorics (p. ex. MILLER, 1984; BAZERMAN, 1988; 2007; SWALES, 1990), and Critical Discourse Analysis (p. ex. FAIRCLOUGH, 1992). The corpus of this study consists of two sets concerning context and text analysis. The analysis focused on context comprehends texts generated and/or selected through participant observation (field notes) and documentary analysis of online publications, directories, and database associated to the CPVAE. In the set of data concerning text analysis, the corpus refers to the transcription of one of the GP/CPVAE encounters, part of a workshop of approximately 15 hours on academic writing, promoted by one of the community participants, on May 15th and 16th 2014. The analysis results reveal an interconnection of two sets of literacy practices: a) requirements from the academic context and b) particularities of the community, to which is attributed a slightly more significant role in the community’s activity system. These results point to two constitutive features of CPVAE’s discourse: 1) as a search for new ways of scientific practice, "scientific research" (materialized in PhD dissertations, thesis, etc.) has, in the activity system of CPVAE, the same status as "art work/production" as they emphasize a subjective point of view and their interdiscursive nature (among science, visual arts, and education); and 2) the resistant discourse in relation to hegemonic discourses emphasizes the search for “novelty” and the coexistence of different perspectives (interdiscursivity), according to a post-modern discourse on science/research. By tensioning the existent paradigms, meeting great resistance from centripetal forces (BAKHTIN, 1952-1953/2003) in VAE, CPVAE finds itself in a state of “scientific revolution” (KHUN, 2012). By evidencing a detachment of CPVAE in relation to the epistemological organization of the disciplinary culture (VAE), our data suggest that academic genre analyses must not only consider the relation between text and context of the disciplinary culture at stake (p. ex., MOTTA-ROTH, 1995; HOOD, 2011), but also and especially the more particular context of the community of knowledge production. Thus, the thesis is that discursive genres associated to academic literacy practices and consequently to LPP processes in communities of knowledge production (as well as pedagogical proposals related to them) must be analyzed in their high degree of situationality (BARTON; HAMILTON, 2000), considering the particularities (associated to the epistemological organization and the system of activities) of the community of practice of which they are part.